Ageisme Verbal Bahasa Jepang Berdasarkan Teori Speaking Dell Hymes - Ai Sumirah Setiawati; Dany Buyung Yudha Prasetya; Irvan Syahid Raharjo Putra (Kajian Linguistik dan Sastra, 2026)
This research aims to analyse how ageism behaviour occurs using Dell Hymes' SPEAKING theory. The data sources for this research are from Japanese animation series, dramas and reality shows. This research was conducted using a qualitative approach, with a qualitative descriptive analysis method carried out in three procedures: (1) data collection, involving note-taking techniques; (2) data analysis using the pragmatic equivalent method, which in its implementation uses Dell Hymes' SPEAKING theory, and; (3) presenting the results of data analysis using an informal presentation method of descriptive data analysis. Based on the data analysis results, 21 Japanese expressions data contained ageism were found. The result of this study shows that verbal act of ageism can occur in the following five ways: (1) in various places and situations; (2) older people towards younger people, and vice versa, even towards oneself; (3) the purpose of the conversation is very influential towards the occurrence of verbal act of ageism, whether intentionally or unintentionally (4) verbal act of ageism occurs in various kinds of speaker intonations whether it high, flat or low, and (5) Most verbal act of ageism occurs in informal conversational setting.